ANALISIS KEMAMPUAN PEMECAHAN MASALAH DAN SELF-REGULATIF SISWA SD DALAM PEMBELAJARAN MATEMATIKA PARENTING - Made Ayu Pransisca; Munawir Gazali (LPPM Institut Pendidikan Nusantara Global, 2022)
Mathematical problem solving ability is the ability of students to find solutions to mathematical problems that cannot be solved immediately or the solution is not yet clear. However, the fact is that student problem solving in Indonesia is still very low. Problem solving is one of the skills that must be mastered by students after learning mathematics. In fact, in elementary school, learning mathematics that develops problem-solving skills has not received much attention from teachers. The teacher's lack of attention to the development of problem-solving skills in the mathematics learning process resulted in students lacking problem-solving skills. One of the learnings that can be done is by applying a mathematics education approach. In addition, students' self-regulation level is still relatively low in learning mathematics. It can be seen from the results of an interview with one of the students of a public elementary school in East Lombok that students still find it difficult to work on questions and do not understand how to do assignments independently. Mathematics parenting learning is one of the new breakthroughs in mathematics learning that can be used by teachers in guiding students to work on math problems independently. The purpose of this study was to analyze the problem-solving and self-regulatory abilities of elementary school students in learning parenting mathematics. This research is a design research research. Design research consists of three phases, namely preliminary design, teaching experiment, and retrospective analysis. This research was conducted at SDN 4 Masbagik Selatan, East Lombok, NTB with research subjects 30 students of class 4A consisting of 14 male students and 16 female students in the 2021/2022 academic year. Data was collected by means of tests (pre-test and post-test) to analyze students' problem-solving abilities in parenting mathematics learning and non-tests (documentation studies, observations, self-regulatory questionnaires, and interviews) were used to analyze students' self-regulatory levels. in parenting mathematics learning. Descriptive statistical analysis was conducted to examine the size of the concentration and distribution of data about the characteristics of the sample/participant and the indicators of the research variables. The data analysis carried out in this study compared the results of the pretest at the preliminary design stage with the results of the post-test at the retrospective analysis stage.